Enhancement of heat transfer in six-start spirally corrugated tubes - Hyder H. Balla (Case Studies in Thermal Engineering, 2017)
The utilization of corrugation for improvement in heat transfer is increasingly becoming interesting recently due to its combined advantages such as extended surfaces, turbulators as well as roughness. This study employed the use of both numerical as well as experimental settings on the water flowing at lower Reynolds numbers in a corrugated tubes with spiral shape to evaluate the performance of heat in a newly designed corrugation style profile. The total performance of the heat for the corrugation tubes were determined and the mathematical information generated from both the Nusselt number and the factors of friction were equated with those of the experimentally generated outcome for both standard smooth as well as the corrugated tubes. Analysis of the dat generated revealed improvements in heat transfer ranges of (2.4–3.7) times those 0btained from the smooth tubes with significant increase in the friction factors of (1.7–2.3) times those of the smooth tubes. Based on the findings of study, it was concluded that for extended period and extensive range use, tubes with severity index values at 36.364×10–3 could produce better heat performance (1.8–3.4) at Reynolds numbers ranging from 100 to 1300. This was an indication that the geometric expression with spiral corrugation profile could significantly enhance the efficiency of heat transfer with significantly increased friction factors.